การประยุกต์ใช้ระบบบริหารคุณภาพ ISO 9001:2008 ในการปรับปรุงคุณภาพการให้บริการน้ำประปาของการประปาเทศบาลตาบลตากฟ้า จังหวัดนครสวรรค์ - Khanthong, Preecha (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 3 (2014): September-December 2014, 2019)
การประยุกต์ใช้ระบบบริหารคุณภาพ ISO 9001: 2008 ในการปรับปรุงคุณภาพการให้บริการน้าประปา เพื่อการปรับปรุงคุณภาพ การให้บริการน้าประปา แก่ประชาชนผู้ใช้บริการน้าประปาในเขตเทศบาลตาบลตากฟ้า และเพิ่มประสิทธิภาพในการปฏิบัติงานของพนักงานอีกทั้งยังช่วยลดการร้องเรียนจากผู้ใช้บริการน้าประปา จากการเก็บข้อมูลความพึงพอใจของผู้ใช้บริการน้าประปาพบว่าการให้บริการน้าประปาด้านสมรรถนะที่มีค่าเฉลี่ยต่ากว่า 2.50 คือความสม่าเสมอ แรงดัน การแจ้งเตือน การหยุดจ่ายน้า การติดตั้งวัสดุอุปกรณ์และการให้บริการน้าประปา ด้านบริการที่มีค่าเฉลี่ยต่ากว่า 2.50 คือ ระยะเวลาการซ่อมแซม กริยามารยาทของพนักงาน ความกระตือรือร้นของพนักงาน การตอบข้อสักถาม จากนั้นผู้วิจัยได้นาข้อกาหนดการบริหารคุณภาพ ISO 9001: 2008 ที่สอดคล้องกับปัญหามาใช้ในการปรับปรุงแก้ปัญหาหลังจากการปรับปรุงโดยการใช้แนวทางการแก้ปัญหาให้สอดคล้องกับข้อกาหนดการบริหารคุณภาพISO 9001: 2008 พบว่า ความพึงพอใจของผู้ใช้บริการน้าประปาต่อการให้บริการเพิ่มขึ้นโดยเฉลี่ย 28.48 % ทั้งนี้ยังเกิดประโยชน์สะท้อนกลับองค์กรอีกครั้งคือเกิดคาชื่นชมจากผู้รับบริการ เกิดภาพลักษณ์ที่ดี ซึ่งทาให้ผู้บริหารเห็นประโยชน์ของการนาระบบนี้มาใช้และจะได้นาระบบบริหารคุณภาพ ISO 9001: 2008 มาใช้ให้สมบูรณ์ในอนาคต คำสำคัญ:  ระบบบริหารคุณภาพ ISO9001: 2008 การประปาเทศบาล การปรับปรุงคุณภาพ           This study focused on the application of the ISO 9001: 2008 quality management system to improve the quality of water supply services for the citizens in Takfa Subdistrict municipality area and to increase the efficiency of the performance of the municipality employees. The application also helped reduce the number of complaints from the public who used the water supply services. From the data regarding the satisfaction of the users of the water supply services in this area, it was found that in terms of the competency, the aspects with the mean scores lower than 2.50 were the consistency, pressure, water-service close alert,equipment installation and water supply services. In terms of services, the aspects with the mean scores lower than 2.50 were the repairment period, employees’ manners, employees’ enthusiasm and responses to queries. Then the researchers implemented the relevant ISO 9001: 2008 quality management system to solve the problems. After the implementation of the problem-solution guideline based on the ISO 9001: 2008 quality management system, it was found that the satisfaction of the service receivers increased on average by 28.48%. Moreover, this implementation yielded another benefit to the organization in that the servicereceivers complimented the services, thus helping create a good organizational image and bringing awareness of the usefulness of implementing this system to the administrators who would make use of the ISO 9001: 2008 quality management system morefully in the future.   Keywords: quality management system, ISO 9001: 2008, municipal waterworks, quality improvement